Dynamic simulation of the water inrush process in tunnel construction using a three-dimensional coupled discontinuous deformation analysis and smoothed particle hydrodynamics method. (September 2022) - Peng, Xinyan; Yu, Pengcheng; Cheng, Xiao; Chen, Guangqi; Zhang, Yingbin; Zhang, Hong; Li, Changze
Graphical abstract: Highlights: Improved contact detection and computing efficiency of 3-D coupled DDA-SPH. Investigated critical condition of a blocking block under water pressure. Studied water pressure induced rock wall movements in tunnel construction. Simulated the water inrush process in tunnel construction. Abstract: Water inrush, which is a major cause of geological disasters during tunnel excavation, can worsen construction conditions and result in casualties. It is thus important to study the water inrush process for mitigating and preventing water inrush disasters in tunnel construction. The tunnel water inrush problem involves solid–fluid interactions. The coupling of the parallel three-dimensional discontinuous deformation analysis (3-D DDA) and 3-D smoothed particle hydrodynamics (3-D SPH) is suitable for analyzing this problem. The critical condition of a block under water pressure was first investigated to check the validity of the 3-D coupled DDA-SPH method. Further, a tunnel water inrush phenomenon was reproduced, and the mechanical behaviors of tunnels were explained with respect to the thickness T of the rock wall, the initial water height H, and the presence and location of a water outlet. The simulation results show that the tunnel deformation increases as T decreases and as H increases. The tunnel deformation was found to be larger when there was a water outlet; however, the location of the outlet had a slight effect on the deformation.